2009
DOI: 10.3109/14647270903377178
|View full text |Cite
|
Sign up to set email alerts
|

The use of a combination of pentoxifylline and tocopherol in women with a thin endometrium undergoing assisted conception therapies – a report of 20 cases

Abstract: An optimal thickness of the endometrium is considered to be one of the prerequisites for successful implantation of the embryo. A retrospective analysis was carried out to investigate the use of Pentoxyfylline and tocopherol in improving the endometrial thickness in cases that are unresponsive to conventional therapy. Twenty women with thin endometrium (<6 mm) undergoing either ovulation induction or frozen embryo transfer cycles were prescribed 800 mg of PTX and 1000 IU of Vit E daily. In 11 cases, the etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 23 publications
0
60
0
Order By: Relevance
“…Low-dose aspirin supplementation in women with impaired uterine perfusion may improve uterine blood flow and lead to pregnancy rates similar to women with normal uterine perfusion [14]. Women with uterine fibrosis or thin endometrium for unknown reasons may benefit from prolonged treatment with pentoxifylline and tocopherol [15,16]. Takasaki et al showed improvement in endometrial thickness and uterine radial artery resistance after treatment with either vitamin E, I-arginine or sildenafil citrate [17].…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose aspirin supplementation in women with impaired uterine perfusion may improve uterine blood flow and lead to pregnancy rates similar to women with normal uterine perfusion [14]. Women with uterine fibrosis or thin endometrium for unknown reasons may benefit from prolonged treatment with pentoxifylline and tocopherol [15,16]. Takasaki et al showed improvement in endometrial thickness and uterine radial artery resistance after treatment with either vitamin E, I-arginine or sildenafil citrate [17].…”
Section: Discussionmentioning
confidence: 99%
“…There are case reports of pregnancies in patients following chemoradiation-induced ovarian failure, who did not respond to hormone replacement therapy, when given the combined pentoxifylline and tocopherol treatment [4244]. 18 oocyte recipients who failed to develop a preovulatory endometrial thickness of >6 mm after receiving vaginal micronized oestradiol were given 6 months of PTX-Vit E treatment.…”
Section: Potential Modalities To Improve Uterine Function After Ramentioning
confidence: 99%
“…Table summarizes the characteristics of the included studies, in which all studies were published between 2002 and 2009. The origins of the studies were one in the United Kingdom (Acharya, Yasmin, & Balen, ), two in France(Ledee‐Bataille et al, ; Letur‐Konirsch et al, ), and one in Iran (Acharya et al, ). In all studies the effectiveness of combination of PTX and Tocopherol was examined on women with a thin endometrium or unable to conceive.…”
Section: Resultsmentioning
confidence: 99%
“…The average age of the participants ranged between 29 and 35. Study samples were 6 (Letur‐Konirsch et al, ), 18 (Ledee‐Bataille et al, ), and 20 (Acharya et al, ), and in one study the total participants were 112 (Aleyasin, Aghahosseini, Mohseni, & Mahdavi, ). The daily dose of PTX was 400 mg in two studies (Aleyasin et al, ; Ledee‐Bataille et al, ) and 800 mg was administered in two studies (Acharya et al, ; Letur‐Konirsch et al, ).…”
Section: Resultsmentioning
confidence: 99%